ACUTE TOXICITY EVALUATION OF ETHANOL EXTRACT OF CURCUMA MANGGA RHIZOME - Yuandani; Suwarso, Edy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Curcuma mangga is highly valued in traditional medicines. This study was carry out to evaluate the in vivo acute toxicity of C. mangga. Methods: Acute toxicity of ethanol extract of C. mangga rhizome was evaluated in mice. The extract at a single dose of 500, 1000, 2000 and 5000 mg/kg body weight (BW) were orally administered to the test animal. Signs of toxicity, BW and mortality were observed for 14 days. The macropathology dan histopathology examination was also performed. Results: The highest dose administered (5000 mg/kg BW) did not produce mortality of the test animals. Hence, the lethal dose 50 of ethanol extract of C. mangga was estimated to be more than 5000 mg/kg. No sign of toxicity was observed except lethargy. All the organs displayed normal color and texture. Histopathological examination did not show any lesion except for highest dose. Conclusion: The results indicate the safety of ethanol extract of C. mangga rhizome to the animal tested. Therefore, this plant can be used as a safe and effective alternative medicine. Keywords: Curcuma mangga, Acute toxicity, Mortality.